KNOWLEDGE LEVEL OF DAIRY FARMERS IN BREEDING MANAGEMENT OF DAIRY ANIMALS (Indian Journal of Animal Production and Management, 2014)
A study was carried out in Virudhunagar district of Tamil Nadu in India to evaluate the knowledge level among the dairy farmers about the breeding practices. In this study, the knowledge index was derived on various parameters related to breeding of dairy animals. From the results of this study, the farmer’s knowledge level about the breed of their own animals, estrus cycle, time of pregnancy diagnosis, symptoms of parturition and gestation period were in an appreciable level. The farmers with more animals (more than 10 animals) followed the scientific principles in the management of dairy animals and their knowledge about the breeding parameters was good.
Keywords: Dairy farming; Breeding; Knowledge level